Phytochemical profiling of commercially important South African plants - Viljoen, Alvaro; Chen, Weiyang; Mulaudzi, Nduvho; Kamatou, Guy; Sandasi, Maxleene (Academic Press, 2021)
"Phytochemical Profiling of Commercially Important South African Plants comprises a carefully selected group of plant species that are of interest to researchers and industry partners who would like to investigate the commercialization of plant species. The book presents 25 botanicals selected based on commercial relevance. For each of the species, the following topics are covered: botanical description and distribution, phytochemistry (including chemical structures), HPTLC fingerprint analysis, UPLC analysis, and GC analysis (the latter only in the case of essential oil-bearing species). Using standard methodology, high-level chromatographic fingerprints have been developed for better understanding. Different methods are succinctly summarized allowing for the rapid identification of botanical raw materials and formulated consumer products. This book will be extremely valuable to researchers in the field who wish to rapidly identify the constituents and for those who want to prepare formulations of plant material for commercial applications. This work will also be a valuable resource in the field of pharmacognosy. Key Features: Comprehensive chemical profiling of each species; Fingerprints developed for non-volatile and volatile constituents; Methods succinctly summarized to ensure reproducibility."--Publisher's description